Pengaruh pemberian minuman campuran daun katuk, daun pepaya, dan kacang hijau terhadap produksi ASI dan berat badan bayi mencit - Iskari Ngadiarti; Muntikah Muntikah; Didit Damayanti (AcTion: Aceh Nutrition Journal, 2021)
Foodstuffs rich in lactogogum are very useful in increasing milk production, especially in postpartum mothers. This study studied the effect of a mixed drink of katuk leaves, papaya leaves, and green beans on increasing breast milk production and weight growth of baby mice. This type of research is an experimental RAL with four treatments and three repetitions on female mice of the DDY strain aged 2,5–3 months, a total of 32 mice with six mice each. Mice were divided into four groups, two treatment groups and two control groups. Its treatment for 12 days postpartum. Data analysis used ANOVA and continued with the Duncan test at a 5% confidence interval. The study results found that there was a significant difference in the average milk production of the mother mice in the four groups (p= 0,003); there was no difference in the average total weight gain of mice during the four groups (p= 0,187). In conclusion, giving a functional drink a mixture of katuk leaves, papaya leaves, and green beans has the same potential as commercial katuk leaf extract but has not increased breast milk production in mice. Suggestion, further research is needed to measure prolactin hormone levels and milk quality